University Support for Student Entrepreneurship in China: Developing Entrepreneurial Capacity and Intentions - Lei Ye; Ting Zhang; Qiong Zhang; Zefeng Mi (SAGE Open)
Recent research has paid considerable attention to the role of university support in explaining student entrepreneurship, with several studies presenting empirical evidence of the moderating effects of individual traits on the relationship between university support and entrepreneurial intentions. However, the moderating effect of entrepreneurial capacity on this relationship has not been considered. This is particularly true in the Chinese context, where college students are reluctant to start businesses despite the substantial entrepreneurial support provided. Grounded in the theory of triadic reciprocal determinism, this study aimed to investigate the link between university support and entrepreneurial intention and examine the mediating role of students’ entrepreneurial capacity. Survey data were collected from 1,058 undergraduates in China’s Anhui Province and analyzed using structural equation modeling with partial least squares estimator. We found a positive but weak effect of university support on students’ entrepreneurial intentions, indicating that students are unlikely to obtain sufficient support directly from a wide range of university resources. However, university support significantly enhanced students’ entrepreneurial capacity, which, in turn, predicted students’ intention to create new enterprises. Our study also found that entrepreneurial capacity played an intermediary role between university support and students’ entrepreneurial intentions. These findings have several practical implications for policymakers and university administrators in terms of enhancing entrepreneurial support and students’ entrepreneurial intentions. This study contributes to the literature on student entrepreneurship in emerging economies.